2010
DOI: 10.1016/j.bbagen.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Decline in mitochondrial bioenergetics and shift to ketogenic profile in brain during reproductive senescence

Abstract: Background We have previously demonstrated that mitochondrial bioenergetic deficits precede Alzheimer’s pathology in the female triple transgenic Alzheimer’s (3xTgAD) mouse model. Herein, we sought to determine the impact of reproductive senescence on mitochondrial function in the normal non-transgenic (nonTg) and 3xTgAD female mouse model of AD. Methods Both nonTg and 3xTgAD female mice at 3,6,9, and 12 months of age were sacrificed and mitochondrial bioenergetic profile as well as oxidative stress markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
145
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(164 citation statements)
references
References 32 publications
17
145
0
2
Order By: Relevance
“…Hypometabolism can be observed in several brain areas, especially in the hippocampus [60,61] as well as impaired mitochondrial function [62]. There is a shift in brain metabolism as an early event in AD pathology, which results in decreased cerebral glucose utilization, while changing from utilization of glucose to increased ketogenesis during aging [63,64]. Providing ketone bodies as an alternative fuel for neurons has been suggested to bypass such metabolic deficits present in the AD brain.…”
Section: Metabolic Therapies In Mouse Models Of Alzheimer`s Diseasementioning
confidence: 99%
“…Hypometabolism can be observed in several brain areas, especially in the hippocampus [60,61] as well as impaired mitochondrial function [62]. There is a shift in brain metabolism as an early event in AD pathology, which results in decreased cerebral glucose utilization, while changing from utilization of glucose to increased ketogenesis during aging [63,64]. Providing ketone bodies as an alternative fuel for neurons has been suggested to bypass such metabolic deficits present in the AD brain.…”
Section: Metabolic Therapies In Mouse Models Of Alzheimer`s Diseasementioning
confidence: 99%
“…The model on female rat brain aging revealed that bioenergetic decline is starting from perimenopausal transition, which is followed by the decrease of brain synaptic plasticity [39]. The mouse female transgenic model of familial AD revealed that ovariectomy induces a shift in fuel availability and metabolism in the hippocampus, with an increase of enzymes required for long-chain fatty acid and ketone body metabolism, to obtain brain energy [46,60]. Glucose hypometabolism associated to cerebral hypoperfusion initiated with perimenopausal atherosclerosis [61], hypercholesterolemia, nitric oxide, and impairment of redox homeostasis is considered as the key pathophysiologic promoter of neurodegeneration [59], and the known differences in regional brain metabolism make some women prone to AD [62].…”
Section: Hypothesis On Brain Aging and Neurodegeneration During Perimmentioning
confidence: 99%
“…It was demonstrated how during reproductive ages the estrogen-induced signaling pathways in hippocampal and cortical neurons converge upon the mitochondria to enhance aerobic glycolysis coupled to the citric acid cycle, mitochondrial respiration, and ATP generation, and in senescence when estrogens are missing, it is a chronic oxidative stress due to the shift from an aerobic glycolytic to a ketogenic profile/phenotype/ [35,60], and this shift is preceded by the early, already mentioned decline in glucose transport and metabolism [46]. In mouse model, the mitochondrial bioenergetic deficit precedes AD [92].…”
Section: Sex Hormones In Neurodegenerative Processes and Diseases 132mentioning
confidence: 99%
“…This may contribute to development of type 2 diabetes mellitus as insulin secretion requires a coupled PDC-OXPHOS system and increasing PDC activity in patients had a glucose and lactate lowering effect (Stacpoole, Moore & Kornhauser 1978). In brain, an age-related decrease in glucose oxidation and oxygen consumption was observed (Kalpouzos et al 2009;Martin et al 1991) together with an increase of aerobic glycolysis and ketone body oxidation (Ross et al 2010;Yao et al 2010). Many neurodegenerative diseases, particularly Alzheimer's disease, are associated with abnormal brain oxidative metabolism and data implicate a reduced PDC activity and up-regulation of aerobic glycolysis (reviewed in (Coskun et al 2012;Green, Galluzzi & Kroemer 2011)).…”
Section: ) (Reviewed In (Stacpoole 2012))mentioning
confidence: 99%
“…Decreased PDC activity reduces glucose carbon flux into the TCA cycle and is linked to various age-related diseases such as glucose intolerance (Stacpoole, Moore & Kornhauser 1978), heart failure (Bersin & Stacpoole 1997), neurodegeneration (Stacpoole 1997), and cancer (reviewed in (Stacpoole 2012). An age-related decrease in glucose oxidation and oxygen consumption was observed in the brain (Kalpouzos et al 2009;Martin et al 1991) together with increased ketone body formation and aerobic glycolysis (Ross et al 2010;Yao et al 2010). Many neurodegenerative diseases, such as Alzheimer's disease, are associated with abnormal brain oxidative metabolism and data implicate up-regulated aerobic glycolysis and reduced PDC activity (reviewed in (Coskun et al 2012;Green, Galluzzi & Kroemer 2011).…”
Section: Tca Cycle and Oxidative Phosphorylationmentioning
confidence: 99%